Keragaman dan Hubungan Ukuran Tubuh Terhadap Produktivitas Sapi Bali (Bos sondaicus) di Kota Samarinda: Diversity and Relationship Morphometrics Toward Productivity of Bali Cattle (Bos sondaicus) at Samarinda City - Nur Rahmatullah, Surya (Universitas Islam Negeri Alauddin Makassar, 2023)
Bali cattle are one of Indonesia's local cattle that are spread throughout Indonesia, accompanied by information on the diversity of morphometrics. The aim of this study was to determine the diversity and relationship between morphometrics and the productivity of bull Bali cattle (Bos sondaicus) in Samarinda City at various ages. The study was conducted from July 2020 to January 2021 in Samarinda City with a sample of bull Bali cattle aged 18 -> 42 months. Data obtained from the measurement of cattle samples which include data on morphometrics and body weight as productivity. The data were then analyzed to obtain the average value, diversity, and analysis of the relationship between productivity and morphometrics. Based on the results of the study, it was found that the chest girth morphometric of bull Bali cattle had the highest coefficient of diversity at various ages, respectively, aged 18-24 months; 24 – 36 months; 36 – 42 months; and > 42 months ie 4.53%; 4.53%; 7.07%; and 3.93%. Based on correlation and regression analysis, it shows that there is a relationship and productivity relationship, namely body weight on morphometrics, namely between chest girth which showed significant results that have the most effect on body weight so that every increase in chest girth will be followed by body weight gain. Diversity in bull Bali cattle in Samarinda city is influenced by several factors such as genetics, environment and management applied to livestock. Diversity can be information in the selection of livestock development.